The marketing potential of the enterprise and the possibilities of its development in modern conditions - N. V. Arsenieva; L. M. Putyatina (Вестник университета)
The article is devoted to the study of the modern concept of “marketing potential” and the possibility of its use for the development of modern enterprises. Scientific research in recent years has studied the concept of “potential” in detail from the point of view of theory and practice. The marketing potential is a relatively new category and its emergence is dictated by the development of modern market relations. The article analyses various approaches to the study of this concept based on the evolution of marketing concept. It is emphasized that all the main approaches to determining the essence of marketing potential are based on orientation to the market and consumers. The relevance and novelty of the research lies in a integrated approach to the concept of “marketing potential”: from the point of view of various approaches, concepts, classification by functional characteristics. The purpose of the study is to determine the features of the modern category of “marketing potential of the enterprise” and their scientific use in the implementation of long-term development plans. The methodological basis of the research is modern scientific developments in the field of management, enterprise economics, marketing management. The marketing of the enterprise should correspond to two main concepts: consumer orientation and orientation to a cost approach to management.